2017
DOI: 10.1155/2017/2929381
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of the Methylation of Multiple Gene Promoters in Serum in Hepatitis B Virus-Related Hepatocellular Carcinoma

Abstract: This study sought to evaluate the diagnostic value of the methylation of multiple gene promoters in serum in hepatitis B virus- (HBV-) related hepatocellular carcinoma (HCC). A total of 343 participants were enrolled, including 98 patients with HCC, 75 patients with liver cirrhosis (LC), 90 patients with chronic hepatitis B (CHB), and 80 healthy individuals. RASSF1A, APC, BVES, TIMP3, GSTP1, and HOXA9 were selected as the candidate genes. The MethyLight method was used to assay promoter methylation statuses. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 29 publications
0
45
0
4
Order By: Relevance
“…Among these 33 publications, 11 articles described the diagnostic role of circulating Ras association domain family 1 isoform A ( RASSF1A ) methylation in HCC and eight articles evaluated the diagnostic performance of ctDNA combined with AFP assay in HCC . Nine articles assessed the diagnostic accuracy of AFP assay for HCC …”
Section: Resultsmentioning
confidence: 99%
“…Among these 33 publications, 11 articles described the diagnostic role of circulating Ras association domain family 1 isoform A ( RASSF1A ) methylation in HCC and eight articles evaluated the diagnostic performance of ctDNA combined with AFP assay in HCC . Nine articles assessed the diagnostic accuracy of AFP assay for HCC …”
Section: Resultsmentioning
confidence: 99%
“… 15 , 16 , 18 , 19 However, there are contradictory results concerning the role of GSTP1 promoter methylation in the progression of HBV-related HCC as well. 17 , 20 In view of the conflicting evidence on this issue, we performed this meta-analysis to evaluate the exact relationship between GSTP1 promoter methylation and increased risk of HBV-related HCC. Consequently, our results confirmed that the methylation rates of GSTP1 gene in cancer tissues were considerably higher than those of normal controls (OR =6.05, 95% CI =1.20–30.52) as well as cirrhosis tissues (OR =5.21, 95% CI =2.19–12.41), suggesting the importance of GSTP1 promoter region methylation in the development of HBV-related HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Так, определение уровня метилирования сайта в гене GSTP1 в ц-ДНК из сыворотки крови при инфекции HCV показало бόльшую специфичность (93,3 %) по сравнению с определением сывороточного АФП (72,7 %) для диагностики ГК [64]. В то же время для пациентов с HBV-ассоциированными ГК индивидуальная диагностическая значимость метилирования сайта в промоторе GSTP1 невысока [34]. Этот биомаркер может быть использован для диагностики ГК в составе мультигенных панелей: по данным W. Huang и соавт., такая мультигенная панель отличается более высоким показателем чувствительности (93,6 %) по сравнению с АФП (48,4 %) [56].…”
Section: обзорные статьиunclassified
“…Гиперметилирование сайтов в промоторе гена RASSF1 в ц-ДНК из крови обладает высокой диагностической значимостью: показатели чувствительности и специфичности составляют 52-75 и 58,9-91,5 % соответственно [33,34,69]. В то же время диагностическая точность панелей биомаркеров метилирования, в состав которых входят сайты в промоторе гена RASSF1 (см.…”
Section: обзорные статьиunclassified
See 1 more Smart Citation